Western flower thrips Frankliniella occidentalis Pergande (Thysanoptera: Thripidae): A newly recorded invasive species in Indonesia - Dedi Hutapea; Dewi Sartiami; Dadang Dadang; Purnama Hidayat (Universitas Lampung, 2025)
The most economically important invasive thrips species, known for causing serious damage to various crops through feeding and virus transmission, was recorded in the cut flower production center of West Java Province, Indonesia. Thrips specimens were collected from chrysanthemum plastic houses using sweep nets, beating trays, yellow pan traps, and hand vacuums. Based on morphological characteristics, the specimens were identified as Frankliniella occidentalis Pergande 1895 (Thysanoptera: Thripidae). Infestation levels in chrysanthemum ranged from 9 to 15 individuals per plastic house. This is the first confirmed report of F. occidentalis infesting chrysanthemums in Indonesia, as the species has not been previously recorded in the country. It can be distinguished from other thrips species by its unique morphological traits, including comb-like setae on the eighth abdominal tergite and distinctive chaetotaxy patterns on the head and pronotum.